Mechanical and elastic properties of vitrified radioactive wastes using ultrasonic technique - Erenturk, Sema Akyil; Gur, Filiz; Aslani, Mahmoud A.A. (Elsevier BV, 2024)
It is important that radioactive and nuclear wastes are immobilized in a glass composition with lower melting temperatures due to their economy. In this study, the elastic and mechanical properties of sodium borate-based vitrified radioactive waste were measured using ultrasonic techniques. Many ultrasonic parameters, such as elastic moduli, Poisson's ratio, and microhardness, were calculated by measuring the ultrasonic velocities of the glasses. The ultrasonic velocity data, the density, the calculated elastic moduli, micro-hardness, softening temperature, and Debye temperature depending on the glass composition were evaluated, and the relation with the structure was clarified. It was observed that the elastic modulus and Poisson ratio increased as the Cs2O content increased in glasses containing Cs waste. This result shows that the rigidity of the network structure of these glasses increases in contrast to the glass containing Sr.
Keywords: Ultrasonic technique; TK9001-9401; Vitrified radioactive waste; Elastic properties; Nuclear engineering. Atomic power; Mechanical properties